2017
DOI: 10.1111/jgs.14764
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preoperative Malnutrition and Postoperative Delirium After Hip Fracture Surgery in Older Adults

Abstract: This is the first study in a Western population showing that risk of malnutrition and overt malnutrition, as assessed using the MNA-SF, are independent predictors of postoperative delirium. Accordingly, nutritional status should be assessed in individuals with hip fracture before surgery to determine risk of developing delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 43 publications
3
94
0
2
Order By: Relevance
“…14 Another study by Mazzola et al showed that the risk of malnutrition and overt malnutrition were significant predictors for POD after hip fracture surgery. 15 Accordingly, they suggested that nutritional status assessment should be performed to help predict POD development. 15 However, few studies have reported their association on clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Another study by Mazzola et al showed that the risk of malnutrition and overt malnutrition were significant predictors for POD after hip fracture surgery. 15 Accordingly, they suggested that nutritional status assessment should be performed to help predict POD development. 15 However, few studies have reported their association on clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…15 Accordingly, they suggested that nutritional status assessment should be performed to help predict POD development. 15 However, few studies have reported their association on clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status requires particular attention in that it has been identified as one of the most sensitive markers of negative outcome; an inadequate nutritional status is a biological signal not so much (and not only) of insufficient food intake but rather of a poor homeostatic reserve. This also explains its role as an independent risk factor of post-procedural mortality [8].…”
Section: Evaluation Of Somatic Disordersmentioning
confidence: 88%
“…Indeed, some mistakes are avoidable, such as the inappropriate use of antihypertensive medications, which often leads to an increased risk of hip fracture occurrence [7]. Other conditions are potentially preventable, e.g., a poor nutritional status, which was associated with the occurence of post-operative delirium in a recent study [8]. Nutritional markers were also used to predict the risk of 30-day readmission among patients hospitalized for hip fracture: according to Stone et al prealbumin, albumin, total protein, and vitamin D levels represent the core part of a statistical model to predict 30-day readmissions [9].…”
Section: To the Editormentioning
confidence: 99%